Pengaruh Jenis Medium Terhadap Kecepatan Penetrasi Panas dan Daya Terima Produk Kalengan Ikan Tuna Skipjack (Katsuwonus pelamis) - Adnan, Mahfid; Ernawati; Maghfiroh, Khoirin (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2022)
Tuna fish has high content of protein. The purpose of food processing is to make a well preserve product, improving the taste and increasing economic value. Sterilization of canned tuna is an example of food processing to achieve the above purpose. A well preserve product must be free from the possibility of proliferation of microorganisms. The objective of this study was to investigate and evaluate the impact of medium used in canned tuna product on heat penetration speed during sterilization and to know the preference level by consumer.Determination of F0 value in this research refers to the protocol of Canadian Food Inspection Agency (CFIA) by using general method to analyse data, protein analysis followed Kjeldahl method and organoleptic examination used Friedman test. Analysis of effectiveness index was conducted to determine the best treatment. The experimental design used randomized single design with three kinds of treatments which were repeated 3 times for each observation. Results indicated that the fastest heat penetration was obtained by in brine product with 46 minutes sterilizatiion time, followed by in oil product with 62 minutes, then in brine + oil product with 65 minutes. Analysis of variance showed that treatment of medium usage provides a very significant impact on heat penetration (F count larger than F table 5 % and 1 %). Heat treatment also provides a significant impact on protein content (F count larger than F table 5 % and 1 %). Organoleptic examination showed that treatment gave significant effect on flavour and odor (F count larger than F table), but not significant on color (F count is smaller than F table). In conclusion, the fastest heat penetration was obtained by in brine product with 46 minutes sterilization time, followed by in oil product 62 minutes, then in brine + oil product with 65 minutes. Consumer preference and the best treatment in this research was obtained by in brine + oil product, followed by in oil product, then in brine product.